The impact of women in the literary life of Gibran Khalil Gibran - Al Tuma, Qayssar Abed Kadhim; Mottaqi, Amir Moqaddam; Seyedi, Seyed Hosein (Linguistics and Culture Review, 2021)
Gibran Khalil Gibran loved women, but he did not love one woman, for he shared his life with a number of women, and these women saw him under different names such as mother, sister, beloved, friend and others, but did Gibran appreciate their great role in the stages of his life and did they influence These women in his literary life and how they affected? This research aims to shed light on this aspect of the life of this writer, answering such two questions, to show the extent of the impact of women in Gibran’s literary life, using the descriptive-analytical approach. And the most important findings of the research. The results are that the woman played a great role in the formation of Gibran’s literary personality, as his works gave a special color and character that differed from the works of others, and this is evident through his writings. This Mary Haskell was unique among all women with the first lover in his literary life, as he still frequently shows his love for her in his words to the point of illusion that he did not love another woman.